OEGylated polypeptide bearing Y-Shaped pendants with a LCST close to body temperature: Synthesis and thermoresponsive properties. (March 2019) - He, Xiongliang; Zhou, Rongtao; Ge, Chenglong; Ling, Ying; Luan, Shifang; Tang, Haoyu
Graphical abstract: We developed a new type of OEGylated polypeptides bearing Y-shaped pendants (8-OEG x, x  = 2, 3) that showed a reversible LCST-type phase transition in a broad polymer concentration range and the LCST-type T cp can be tuned close to human body temperature. We have demonstrated that the water-solubility and LCST-type T cp can be improved by incorporation of Y-shaped and OEG pendants due to the increment of hydrophilicity. Highlights: We prepared OEGylated polypeptides bearing Y-shaped pendants. We studied the structure and thermoresponsive properties relationship. Polypeptide bearing Y-shaped pendants showed significantly increased hydrophilicity than the linear shaped counterpart. Abstract: The understanding of molecular structure and thermoresponsive property relationships and development of water-soluble thermoresponsive polymers with tunable cloud point temperatures ( T cp s) are crucial toward versatile practical uses. Herein, OEGylated polypeptides bearing Y-shaped pendants, namely poly(γ-4-(propoxycarbonyl)benzyl-L -glutamate)-oligo(ethylene glycol) conjugates (8-OEG x, x  = 2, 3) were synthesized by the combination of ring-opening polymerization of γ-4-(allyloxycarbonyl)benzyl-L -glutamic acid based N -carboxyanhydride (4 ) and subsequent side-chain modifications, including bromination of poly(γ-4-(allyloxycarbonyl)benzyl-L -glutamate) (5 ), nucleophilic substitution of5 in the presence of NaN3, and subsequent copper-mediated 1, 3-dipolar cycloaddition. Both 1 H NMR and FTIR analysis confirmed the molecular structures of the intermediates and 8-OEG x . In aqueous solutions, 8-OEG x samples showed reversible lower critical solution temperature (LCST)-type phase transitions in broad polymer concentration range (0–30 mg·mL −1 ). Variable-temperature UV–vis spectroscopy results revealed that the LCST-type T cp of 8-OEG2 at high polymer concentrations (e.g., ≥10 mg∙mL −1 ) was in the range of 37.5–42.5 °C. 8-OEG2 showed a remarkable increase of hydrophilicity than PBLG-OEG4 with the same amount of OEG units as well as linear shaped pendants. The T cp of OEGylated polypeptides increased by addition of NaI, yet it decreased upon addition of NaCl, NaBr, or KCl, which obeys the Hofmeister effect.